The Impact of Digital Transformation on Talent Recruitment Strategies in Modern Human Resource Management - Sunardi Ginting; Karno Diantoro; RR Roosita Cindrakasih; Roy Mubarak; Suseno (Politeknik Ganesha Medan, 2023)
Along with technological advances, digital transformation has become a major phenomenon in various sectors, including in the business world and human resource management (HRM). HRM is undergoing a major revolution in addressing digital transformation. This research aims to examine the impact of digital transformation on talent recruitment strategies in modern human resource management. The method includes a thorough examination of literature using qualitative analysis, with the aim of gaining a comprehensive comprehension of the topic spanning from 2017 to 2023. The study results show that digital transformation has significantly changed the paradigm of talent recruitment in human resource management (HRM). From the use of digital platforms to the application of artificial intelligence (AI) and data analytics, companies must constantly adapt to stay competitive and attract the best talent. More efficient recruitment processes, empowerment of job seekers, and the possibility of work flexibility are positive outcomes of this transformation. However, ethical challenges such as bias in algorithms and the protection of personal data also need serious attention.